The Role of Municipalities in Managing Disasters in International Experiences: A Comparative Study - Mohauish, Sultan; Ashmawy, Iman (The Arab Journal of Administration, 2022)
Purpose – This study aims to explain the roles of municipalities in managing local disasters in some international experiences by identifying the different agencies entrusted with crises management and the extent of coordination or conflict between these agencies. Design/methodology/approach - This study is depended mainly on comparative approach, which used in analyzing local disaster management in some international experiences located in different geographical places, namely the experiences of the United States, India, South Africa and Australia. Findings - The study concluded some findings, the most important of which are: The necessity of having an independent authority concerned with local disaster management, providing financial and political support for this authority, and finally supporting local and central coordination mechanisms between all parties participating in managing local disasters. Practical Implications - The study reflects one of the most important studies working to achieve sustainable development in developing countries such as Saudi Arabia. This study also provides a framework and vision to help municipalities in developing countries to rebuild stronger and more inclusive capabilities in post-disaster stage which help these countries to overcome the harmful effects of local disasters they face.